CRAFTER: Reviving Bronze Age Pottery in EU-funded Project - Carlos Velasco Felipe; Miguel Valério (EXARC Journal)
The CRAFTER project aims at reviving modern-day artisanship by drawing inspiration from pottery traditions of four of the most remarkable Bronze Age societies of Europe: El Argar (south-eastern Spain), Únětice (Central Europe), Füzesabony (eastern Hungary) and Vatin (south Serbia).